Enhancement of mucosal innate and adaptive immunity following intranasal immunization of mice with a bovine adenoviral vector - Sayedahmed, Ekramy E.; Elshafie, Nelly O.; Zhang, GuangJun; Mohammed, Sulma I.; Sambhara, Suryaprakash; Mittal, Suresh K. (Frontiers in Immunology, 2023)
Nonhuman adenoviral (AdV) gene delivery platforms have significant value due to their ability to elude preexisting AdV vector immunity in most individuals. Previously, we have demonstrated that intranasal (IN) immunization of mice with BAd-H5HA, a bovine AdV type 3 (BAdV3) vector expressing H5N1 influenza virus hemagglutinin (HA), resulted in enhanced humoral and cell-mediated immune responses. The BAd-H5HA IN immunization resulted in complete protection following the challenge with an antigenically distinct H5N1 virus compared to the mouse group similarly immunized with HAd-H5HA, a human AdV type 5 (HAdV5) vector expressing HA. Here, we attempted to determine the activation of innate immune responses in the lungs of mice inoculated intranasally with BAd-H5HA compared to the HAd-H5HA-inoculated group. RNA-Seq analyses of the lung tissues revealed differential expression (DE) of genes involved in innate and adaptive immunity in animals immunized with BAd-H5HA. The top ten enhanced genes were verified by RT-PCR. Consistently, there were transient increases in the levels of cytokines (IL-1α, IL-1β, IL-5, IL-6, TNF-α, LIF, IL-17, G-CSF, MIP-1β, MCP-1, MIP-2, and GM-CSF) and toll-like receptors in the lungs of the group inoculated with BAdV vectors compared to that of the HAdV vector group. These results demonstrate that the BAdV vectors induce enhanced innate and adaptive immunity-related factors compared toHAdV vectors in mice. Thus, the BAdV vector platform could be an excellent gene delivery system for recombinant vaccines and cancer immunotherapy.